Relation between Elevated Plasma Retinol Binding Protein-4 & Glucose Dysregulation in Type 2 Diabetes (Islami Bank Medical College Journal, 2013)
DOI: http://dx.doi.org/10.3329/ibmcj.v2i1.17312 IBMC J 2011; 2(1): 17-20